EFEK PENERAPAN KONTROL AKTIF BLOWING TERHADAP TARIKAN AERODINAMIKA MODEL KENDARAAN - Rauf, Wawan; Rifal, Moh; Pido, Rifaldo; Boli, Rahmad Hidayat; Haris, Zulfikar Abd (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
Vehicle stability when driving is an issue that needs attention because it relates to comfort in driving and the effectiveness of fuel consumption. This is caused by the large aerodynamic drag force of the vehicle due to the structure of the air flow which flows regularly and experiences separation when it reaches the rear end point of the vehicle. This separation of the flows causes significant negative pressure on the rear window due to the return flow which does not follow the shape of the vehicle body. The purpose of this study was to analyze the effect of implementing active control of blowing type flow on vehicle models on aerodynamic drag. This study applies a numerical computational method with a modified Ahmed body model as the main object of research. The active blowing control is placed at the rear end of the model which is considered the initial separation area. Blowing speed was varied 0.2 m/s, 0.8 m/s, 1.5 m/s, and 2.0 m/s and was tested at an upstream speed of 16.7 m/s. Research results indicate that the application of active blowing control has succeeded in providing a delay in separation effect, reducing turbulence and reducing aerodynamic drag by 8-9%.